SENTENCE STRUCTURE ERROR IN WRITING NARRATIVE PARAGRAPH - Impiani Zagoto; Restu Damai Laia; Senadaman Wau (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Narrative paragraph is a kind of paragraphs that tells events in the order they happened. It can be imaginary or based on the real incident. In writing the paragraph, however, the students made errors in sentences structure. The purpose of this study was to find out the errors made by third semester students of English Department at Nias Raya University. This is was a kind of qualitative research which explained the errors found. The result of this study showed that the sentence errors were on subject-verb agreement, and fragments. Moreover, the students were error in the use of punctuations comma (,) and semicolon (;) in compound sentence. Therefore, it is concluded that leaving out the subject/verb/ both and wrong orders of the grammatical elements of a sentence, and misusing the punctuations cause the error in writing narrative paragraph.